Association of apolipoprotein B and adiponectin receptor 1 genes with carcass, bone integrity and performance traits in a paternal broiler line - Cruz, Valdecy Aparecida Rocha da [UNESP]; Schenkel, Flávio Schramm; Savegnago, Rodrigo Pelicioni [UNESP]; Grupioni, Natalia Vinhal [UNESP]; Stafuzza, Nedenia Bonvino [UNESP]; Sargolzaei, Mehdi; Ibelli, Adriana Mércia Guaratini; Peixoto, Jane de Oliveira; Ledur, Mônica Corrêa; Munari, Danísio Prado [UNESP] (Public Library Science, 2015)
Apolipoprotein B (APOB) and Adiponectin Receptor 1 (ADIPOR1) are related to the regulation of feed intake, fat metabolism and protein deposition and are candidate genes for genomic studies in birds. In this study, associations of two single nucleotide polymorphisms (SNPs) g.102A>T (APOB) and g.729C>T (ADIPOR1) with carcass, bone integrity and performance traits in broilers were investigated. Genotyping was performed on a paternal line of 1,454 broilers. The SNP detection was carried out by PCR-RFLP technique using the restriction enzymes HhaI for the SNP g.729C>T and MslI for the SNP g.102A>T. The association analyses of the two SNPs with 85 traits were performed using the restricted maximum likelihood (REML) and Generalized Quasi-Likelihood Score (GQLS) methods. For REML the model included the random additive genetic effect of animal and fixed effects of sex, hatch and SNP genotypes. In the GQLS method, a logistic regression was used to associate the genotypes with phenotypes adjusted for fixed effects of sex and hatch. The SNP g.729C>T in the ADIPOR1 gene was associated with thickness of the femur and breast skin yield. Thus, the ADIPOR1 gene seems implicated in the metabolism and/or fat deposition and bone integrity in broilers.